(untitled) (One Health & Risk Management, 2021)
Introduction. Viral hepatitis A (VHA) is an acute, self-limited, caused by the hepatitis A virus which belongs to the genus Hepatovirus. VHA continues to be a widespread infection on all continents, with the highest prevalence in children - 75-80%. In France, the annual morbidity through viral hepatitis A is 1.5‱, in Romania is 20.08‱ and in Russian Federation is 5.46‱. More often, VHA is spread in poor countries and poor hygienic. The aim of the study is to analyze the multiannual morbidity of VHA and clinical peculiarities of patients hospitalized with VHA infection. Material and methods. This research is a descriptive observational epidemiological study, in which morbidity data of VHA were analyzed. The following were used as information sources: Form 2 of registration and evidence of diseases for the years 2004-2019 and patients diagnosed with VHA during 2016-2020 years, hospitalized in the infectious hospital for children from mun. Chisinau. During this period where hospitalized 40 patients with VHA. The following epidemiological indicators were analyzed: distribution of cases by age groups, gender, living environment, seasonal distribution. Results. Analyzing the multiannual dynamics morbidity of viral hepatitis A in the Republic of Moldova during the 2004-2019 years, we found a decrease in morbidity from 84.0‱ in 2004 to 2.05‱ in 2019, the multiannual average morbidity being 13.16‱. In mun. Chisinau, during the 2004-2019 years, morbidity had a pronounced decreasing trend from 48.08‱ in 2004 to 0.36‱ 2019, with an average of 6,28‱. Depending on the residence place, we found an increased prevalence of the number of cases in rural areas with an average of 16.77‱, but in urban areas, the average morbidity was 7.62‱, being approximately 2.2 times lower than in rural areas. The average incidence of viral hepatitis A is much higher among children – 51.42‱, compared to 4.66‱ among adults. Following the study conducted on the basis of medical records, we found that the peak incidence of viral hepatitis during the 2016-2020 years, was recorded in October-December months. Most parents have requested medical help on the 2nd - 5th day of the disease, and average length of stay was 14 days. Most of the children who were diagnosed with viral hepatitis A, attended an educational institution, 26 children (65.0%) attended school and 12 children (30.0%) attended kindergarten. During the 2016-2020 years, there was a predominance of the 7-17 years age group with 27 registered cases (67.5%), followed by the 3-6 years age group with 10 cases (25.0%), and only 3 cases of viral hepatitis A were registered in the 0-2 years age group. Out of 40 patients, 34 developed jaundice, 6 patients - non-jaundice form of the disease. The jaundice form is about 5.6 times more common than the non-jaundiced. The diagnosis of viral hepatitis A was established by ELISA method. The treatment of VHA is mainly symptomatic and has an important detoxifying role, also being used hepatoprotectors and enzymatic drugs. Conclusions. Over the past year’s incidence of hepatitis A is decreasing, with an average morbidity of 13.16‱. The most affected are children aged 7-17 years who attend the school. The most common among hospitalized children is jaundiced form with an average of 14 days of hospitalization.